The People versus Paul Crump [videorecording (DVD)] - Friedkin, William; Friedkin, William; Smith, John Justin, 1919-1989 (Reel Chicago, 2014)
Paul Crump, who robbed the Chicago stockyards on March 20, 1953, with four other black men, shot one guard to death. He was sentenced to die in the electric chair. William Friedkin met Crump in the Cook County Jail. Friedkin was impressed by the "model prisoner", Crump. Friedkin produced this documentary as an impassioned plea for Crump's return to society.